Pemberdayaan kelompok wanita nelayan melalui olahan ikan laut di Desa Corowali, Barru - Ernawati S. Kaseng (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Abstract. The purpose of community devotion through the Community partnership Program, is to provide the knowledge and diversification skills of marine fish into the sweetened soft-barbed sea fish to the group of women fishermen Corowali 1 as a partner of PKM. In hopes of motivating fishermen housewives and dropouts of young women as well as managers and group members to develop marine fish processed products. The method of implementing the Community Partnership Program (PKM), namely through training, demonstration, and mentoring equipped with learning by doing techniques. For the enhancement of the knowledge and skills of the group of women fishermen and village communities especially mothers of housewives and young women dropouts then the approach is used that approach the Partisipatory Rural Appraisal (PRA). Results of the PKM activities show that the increasing knowledge and skills of Farmer's housewives and young women are dropouts about the benefits and nutritional values contained in marine fish, and how to choose the marine fish that can be combined. Similarly, the process or the way of making sweet pindang soft fish barbed sea and the emergence of the entrepreneurial soul of trainees and society during the mentoring.